A Brassica miRNA Regulates Plant Growth and Immunity through Distinct Modes of Action - Cui, Chen; Wang, Jing-Jing; Zhao, Jian-Hua; Fang, Yuan-Yuan; He, Xiang-Feng; Guo, Hui-Shan; Duan, Cheng-Guo (Molecular plant, 2020)
In plants, high disease resistance often results in a reduction of yield. Therefore, breeding crops with balanced yield and disease resistance has become a major challenge. Recently, microRNA (miRNA)-mediated R gene turnover has been shown to be a protective mechanism used by plants to prevent autoimmunity in the absence of pathogens. However, whether these miRNAs play a role in plant growth and how miRNA-mediated R gene turnover responds to pathogen infection have rarely been explored. Here, we found that a Brassica miRNA, miR1885, targets both an immune receptor gene and a development-related gene for negative regulation through distinct modes of action. MiR1885 directly silences the TIR-NBS-LRR class of R gene BraTNL1 but represses the expression of the photosynthesis-related gene BraCP24 by targeting the Trans-Acting Silencing (TAS) gene BraTIR1 for trans-acting small interfering RNAs (tasiRNAs)-mediated silencing. We found that, under natural conditions, miR1885 was kept at low levels to maintain normal development and basal immunity but peaked during the floral transition to promote flowering. Interestingly, upon Turnip mosaic virus (TuMV) infection, miR1885-dependent trans-acting silencing of BraCP24 was enhanced to speed up the floral transition, whereas miR1885-mediated R gene turnover was overcome by TuMV-induced BraTNL1 expression, reflecting precise regulation of the arms race between plants and pathogens. Collectively, our results demonstrate that a single Brassica miRNA dynamically regulates both innate immunity and plant growth and responds to viral infection, revealing that Brassica plants have developed a sophisticated mechanism in modulating the interplay between growth, immunity, and pathogen infection. The trade-off between growth and defense has long been a major challenge in crop breeding. This work demonstrates that a Brassica miRNA, which is subject to dynamic regulation during development and responds to viral infection, regulates immunity and development through distinct modes of action.